Lipoxins modulate neutrophil oxidative burst, integrin expression and lymphatic transmigration differentially in human health and atherosclerosis. Issue 3 (1st February 2022) - Kraft, Jamie D.; Blomgran, Robert; Bergström, Ida; Soták, Matúš; Clark, Madison; Rani, Alankrita; Rajan, Meenu Rohini; Dalli, Jesmond; Nyström, Sofia; Quiding‐Järbrink, Marianne; Bromberg, Jonathan; Skoog, Per; et al.
Abstract: Dysregulated chronic inflammation plays a crucial role in the pathophysiology of atherosclerosis and may be a result of impaired resolution. Thus, restoring levels of specialized pro‐resolving mediators (SPMs) to promote the resolution of inflammation has been proposed as a therapeutic strategy for patients with atherosclerosis, in addition to standard clinical care. Herein, we evaluated the effects of the SPM lipids, lipoxin A4 (LXA4 ) and lipoxin B4 (LXB4 ), on neutrophils isolated from patients with atherosclerosis compared with healthy controls. Patients displayed altered endogenous SPM production, and we demonstrated that lipoxin treatment in whole blood from atherosclerosis patients attenuates neutrophil oxidative burst, a key contributor to atherosclerotic development. We found the opposite effect in neutrophils from healthy controls, indicating a potential mechanism whereby lipoxins aid the endogenous neutrophil function in health but reduce its excessive activation in disease. We also demonstrated that lipoxins attenuated upregulation of the high‐affinity conformation of the CD11b/CD18 integrin, which plays a central role in clot activation and atherosclerosis. Finally, LXB4 enhanced lymphatic transmigration of human neutrophils isolated from patients with atherosclerosis. This finding is noteworthy, as impaired lymphatic function is now recognized as an important contributor to atherosclerosis. Although both lipoxins modulated neutrophil function, LXB4 displayed more potent effects than LXA4 in humans. This study highlights the therapeutic potential of lipoxins in atherosclerotic disease and demonstrates that the effect of these SPMs may be specifically tailored to the need of the individual.